(untitled) (Researcher CAB: A Journal for Research and Development, 2023)
As modern societies evolve, entrepreneurial sustainability becomes increasingly relevant and applicable across developed and developing countries worldwide. The issue of corporate social responsibility (CSR) in business has grown significantly, and it has been identified as a strategic weapon for entrepreneurship growth today. Thus, the present study attempted to examine CSR’s influence on entrepreneurship development. Carroll’s four social responsibilities in this study can be considered as CSR: economic, legal, ethical, and philanthropic. The study followed a positivist research paradigm, deductive reasoning, a causal-comparative research method, and convenience sampling techniques for its procedural operations. The study’s target population was the total number of registered small and medium-sized enterprises (SMEs) in Dailekh District. The study incorporated 465 business owners as the sample size. The structured survey questionnaire was used to collect the primary data. The data were analyzed using descriptive and inferential statistics like percentages, frequency, and structural equation modeling. In order to analyze the data, SPSS 20 and AMOS 23 were used. The results of the study demonstrated that there is a significant positive impact of CSR on entrepreneurship development. Therefore, the concerned stakeholders should consider preserving CSR in their businesses. In addition, the study’s results will be a source of information for stakeholders like entrepreneurs, customers, researchers, and academicians.